Expanding the repertoire of cyclopropenium ion phase transfer catalysis: Benzylic fluorination. Issue 27 (5th July 2018) - Dempsey, Katie; Mir, Roya; Smajlagic, Ivor; Dudding, Travis
Abstract: The application of cyclopropenium ion as a phase transfer catalyst for benzylic fluorination in high yields is reported. Integral to the mechanisms of these fluorination reactions was the role of in situ derived cyclopropenium fluoride complexes, the existence of which was supported by 1 H, 19 F NMR and UV–Vis spectroscopy. Density functional theory calculations were applied to gain insight into the mechanism of these reactions. Graphical abstract: Image 1